Railroads in the Old South Pursuing Progress in a Slave Society - Marrs, Aaron W. (Johns Hopkins University Press, 2009)
Aaron W. Marrs challenges the accepted understanding of economic and industrial growth in antebellum America with this original study of the history of the railroad in the Old South. Drawing from both familiar and overlooked sources, such as the personal diaries of Southern travelers, papers and letters from civil engineers, corporate records, and contemporary newspaper accounts, Marrs skillfully expands on the conventional business histories that have characterized scholarship in this field. He situates railroads in the fullness of antebellum life, examining how slavery, technology, labor, social convention, and the environment shaped their evolution. Far from seeing the Old South as backward and premodern, Marrs finds evidence of urban life, industry, and entrepreneurship throughout the region. But these signs of progress existed alongside efforts to preserve traditional ways of life. Railroads exemplified Southerners' pursuit of progress on their own terms: developing modern transportation while retaining a conservative social order.Railroads in the Old South demonstrates that a simple approach to the Old South fails to do justice to its complexity and contradictions.